Avaliação do potencial antioxidante e citotóxico das partes do fruto de Cereus jamacuru DC, CACTACEAE - Brito, Mônica Silva de (2015)
Cacti are resistant plants during dry periods, among which is included the Cereus jamacaru, known as mandacaru. The mandacaru is a common columnar cactus in Brazil that produces an edible, red, fleshy fruit, with white flesh and small seeds. The fruits to providing essential nutrients and they also produces active ingredients with biological properties such as antioxidant activity. The main objective of the study was to evaluate the antioxidant potential, cytotoxicity and verify the chemical composition of parts of the fruit of Cereus jamacaru DC, aimed at encouraging the consumption and the industrial use of the fruit. Parts of the fruit were separated (peel, pulp and seeds) and made extraction with ethanol 70% and 95%, resulting in six samples: peel (CM70% and CM95%) pulp (PM70% and PM95%) and seeds (SM70% and SM95%). The antioxidant activity was evaluated through sequestration method free radical DPPH (2,2-diphenyl-1-picrilhidrazila). The six samples were tested in concentrations of 100 to 2000 μg mL-1. The positive controls were eugenol and β-carotene. We calculated the percentage of antioxidant activity (AA%) and the Efficient Concentration (EC50). The kinetic profile was determined by the reduction of DPPH with respect to time. The chemical characterization of the samples was performed by infrared spectroscopy (FTIR). The cytotoxicity was determined by MTT assay on macrophages. With the data obtained by infrared, it was found that the six samples show different antioxidant compounds. The peel samples showed AA% values higher than β-carotene in all tested concentrations. Already the SM70% and SM95%% exhibited the highest AA%, with antioxidant activity similar to eugenol in concentrations above of 400 μg mL-1. The samples exhibited three kinetic profiles: fast for SM70%, SM95%, and CM70%; intermediate for the CM95% and slow for PM70% and PM95. The lower EC50 values were observed in seeds and peel samples: SM70% (0,233 mg mL-1) SM95% (0,217 mg mL-1); CM70% (0,56mg mL-1), and CM95% (0.94 mg mL-1). The highest EC50 values were observed in pulp samples: PM70% (10.95 mg mL-1) and PM95% (8,73mg mL-1). Samples of skin and seeds had lower EC50 values than various fruits and seeds known for their antioxidant activity. Only the CM70% showed levels of cytotoxicity in the three highest concentrations, the other samples showed no cytotoxicity at higher concentrations and increased cell viability. Thus we conclude that the mandacaru fruit has compounds with potent antioxidant capacity and could be used by the industry for fresh consumption in the form of juice, pulp, or extraction of antioxidant compounds that can later be used as additives in food.